Community Needs Assessment for Developing a Culturally Responsive STEAM Activity Guide in Dusun Bengkung Magelang - Nora Saiva Jannana; Najwa Husna Nur Syifana (Lembaga Sosial Rumah Indonesia, 2026)
Purpose – This study assesses community needs to inform the development of a culturally responsive STEAM (Science, Technology, Engineering, Arts, and Mathematics) activity guide for a rural non-formal learning context in Dusun Bengkung, Magelang. The study addresses gaps in community readiness, preferred STEAM domains, and practical constraints relevant to guide development.Methods – The study used a descriptive survey as a community needs assessment. Data were collected through a Google Forms questionnaire from youth aged 12-25 in Dusun Bengkung (n = 22) and analyzed descriptively to map respondent characteristics, familiarity with STEAM, domain preferences, perceived barriers, and expectations for future activities.Findings – Most respondents had heard of STEAM (68.2%), although their understanding of its elements varied. Interest was highest in Technology (31.8%) and Arts (27.3%). The most frequently reported participation barriers were limited facilities (31.8%), limited initial knowledge (31.8%), and time constraints (31.8%). Taken together, these findings indicate that the proposed guide should priorities low-cost, beginner-friendly, and hands-on activities, especially those integrating technology and arts, using simple locally available materials and facilitation structures that fit the community context. Research Implications – The findings provide an empirical basis for specifying early design priorities for a culturally responsive STEAM activity guide in a TBM-related context. However, the study is limited by its small single-site sample, reliance on self-reported data, and descriptive design. The results therefore cannot support subgroup comparisons or broader community generalisation. This article reports only the needs assessment stage; further research is required to develop, validate, pilot, and evaluate the guide.